Peranan Transformational Leadership untuk Mengurangi Konflik dalam Hubungan Keagenan - Nur Fadjrih Asyik (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
Principal–agent framework has paradigm used widely in accounting and economic to analize issues about performance evaluation, management controlling, and incentive system design (Jensen and Meckling, 1976). Due to leadership, agency relationship delegate power from leader to subordinate. Leader control subordinate’s performance with accountability mechanism. Another side, there is uncertainty in the business environment. Due to with this condition, vision is needed in order to there is a better change. Organization which can survive and growth is organization has leader with the vision to do changing sharply so leader able transformate organization capabilities to build competitive advantage of the firm (Kotter, 1996). Due to conflict of interest between leader and subordinate in agency relationship, transformational leadership style is convinced able to direct to superior performance in organization with four ways are idealized influence, inspirational motivation, intellectual stimulation, and individualized concideration (Bass and Avolio, 1994). Keywords: transformational leadership, agency relationship